A Comparison of Imaging Outcomes From 2 Weightbearing CT Modalities. - Smolinski, Michael P.; Amadio, Joeseph; Prisk, Victor; Conti, Stephen F.; Miller, Mark Carl (Foot & Ankle International, 2023)
Background: The use of weightbearing images to diagnose foot and ankle injuries continues to offer hope for improved insight into pathologies, but weightbearing CT imaging has been limited by availability. The ability to apply force to the lower limb in a horizontal bore CT system may offer an adaptation to currently available imaging systems that provides access to weightbearing images without the acquisition of additional expensive imaging space or equipment. Methods: In order to determine whether a horizontal CT system could produce the same results as a standing CT, 3 images of one foot from 10 subjects was obtained and standard measures were calculated. Each subject underwent a standing CT scan, a scan in a horizontal bore CT machine while the subject pressed against a pedal with spring resistance and a finally a scan with the foot placed on the pedal but without any pressure. Results: No statistically significant difference between the standing and pedal-based CTs resulted. Navicular height and Meary angle (axial) were statistically different from nonweightbearing for both standing and horizontal systems. The horizontal results were statistically different from nonweightbearing in IM angle, talocalcaneal angle, and talonavicular coverage. No differences from nonweightbearing were found for either system in talar tilt, talocrural angle, or the lateral Meary angle. Conclusion: The results in this initial study of normal control subjects suggest that a pedal-based loading mechanism may adapt a horizontal-bore CT system for the acquisition of weightbearing images. Clinical Relevance: The ability to acquire a weightbearing CT from a horizontal bore CT machine can make these images more available.